Design and Calibration of Five- Holed Conical Probe for Fluid Velocity Measurements in Three Dimensions - Alshamma, Kamil (Basrah Journal for Engineering Sciences, 2012)
The performance of a five-holed conical probe ( which has a conical head with four holes symmetrically placed on the cone surface and one at the truncated tip) for the measurements of fluid velocity in three dimensional incompressible flow was investigated in air in an open circuit subsonic wind tunnel . The air velocity ranged from 15 – 45 m/s and the Reynolds number ranged from 40000 to 100000 based on the cone base diameter. The methods of calibration and use of the probe are given where the measurements of one angle and three pressures are sufficient to give the three components of velocity, static and total pressure. The conical head probe is easier to manufacture than the spherical head probe and has the advantage of having clear fluid separation points at the cone base whereas the fluid separation on the spherical probe is not well defined and depends on the Reynolds number.